Failure analysis of gears, shafts and keys of centrifugal washers failed during life test. (September 2017) - Lanzutti, A.; Gagliardi, A.; Raffaelli, A.; Simonato, M.; Furlanetto, R.; Magnan, M.; Andreatta, F.; Fedrizzi, L.
Abstract: This work presents a failure analysis of a transmission gearbox used in a motor of a food centrifugal dryer tested with a life test procedure developed by Electrolux Professional. The test apparatus consisted in a prototype of the centrifugal dryer where some aluminum cylinders were installed on the drying basket in order to simulate the maximum loads, that in-service are transferred by the food processed in the dryer to the transmission system investigated in this work. This system is employed for the motion of the basket trough an electric motor. The aim of this test apparatus was to simulate the service conditions of the components in order to evaluate their mechanical resistance and to verify that the life of the appliance is consistent with the project specifications. Moreover, the life-test presented in this paper can be used to test new materials for this specific application. The gear and the shafts analyzed in this work are made of low-alloyed steel heat treated by induction quenching followed by tempering. Premature failures occurred during the life test are considered in this work. In particular, the components interested by failure are the gear's teeth or the keys used to transfer force from the shaft to the gear. The failure of these components was observed after about 3000 of ON-OFF cycles. The microstructure of the gears and shafts, that exhibited premature failure together with that of intact components, was investigated by optical microscopy. The chemical composition of these components was characterized by means of Rf-GDOES (Glow Discharge Optical Emission Spectroscopy). The mechanical properties of the components were investigated by Vickers micro-hardness tests. The experimental results obtained in this work indicate that the failure of the components could be related to the quality of the materials of the components. In particular, the life test used in this work proved to be an important tool to evaluate the risk of a possible reduction of the products life due to non-conformity with materials specifications. Highlights: An innovative life test used to design and test the gear boxes of a food processor Examples of failures occurred on some gear boxes, concerning the material quality. Description of the test method in terms of test conditions